Meningkatan Keterampilan Motorik Kasar Melalui Permainan Sederhana - Andhika, Dwi Agung; Prayoga, Aba Sandi; Darumoyo, Kuncoro (Jurnal Porkes, 2022)
This reserach aims to improve student’s motoric gross through applying of simple games to the students  in the academic year of 2021/2022.. The subjects were 21 students of PAUD Al-Kautsar Ngawi who consist of 11 male students and 10 female students.1The data were collected from the researcher, collaborator, and students using tests and observations. The data were validated using data source triangulation technique, and analysed using descriptive analysis technique.1Learning student’s through applying of simple games can improve student’s motoric gross in PAUD Al-Kautsar in the academic year of 2021/2022.  In the beginning condition, there were 4,76% or 1 of students who had learning achievement in good cindition, 33,34% or 7 of students who had learning achivement in fair category, 47,62% or 10 of students were in poor category, 14,28% or 3 of students were in very poor caterory, and the number1of students who passed the passing grade were only 8 students. In the first cycle, there were 4,76 % of students who had motoric gross in good category, 61,91% of students were in fair category, 28,57% of students were in poor category and 4,76% of students were in very poor category, and the number of students who passed the passing grade were 14 students. While in the second cycle, there were 4,76% of students who had motoric gross in very good category, 19,05% of students who had learning achivement in good category, 61,91% of students were in fair category, 14,28% of students were in poor category, and the number of students who passed the passing grade were 18 students.The conclusion of this research is the use of simple games can improve student’s motoric gross at PAUD Al-Kautsar Ngawi in the academic year of 2021/2022.